PERFORMANCE ANALYSIS OF WEB SERVICES BY USING J METER PERFORMANCE TOOL (International Journal of Engineering and Computer Science, 2013)
In this paper we have discussed web services performance and compares the performance differences of web services development approaches in java, Soap API and business logic EJB, is use POJO for access request and pass this object request with data server or server, response back to client which is time consuming in middle layer. Hibernate gives the solution by mapping data directly with data server or server. After developed that application, we have analyzed web services performance by using Apache J Meter web services performance analysis tool that configure IP request address of web services in the form of SOAP xml format and get a response from web services in term of throughput, standard deviation, error, average, median. WSDL contains the information like request for service, IP address and port number of called web services. Performance analyses result can be used to make appropriate choice for developing and optimizing mechanism to web services environment.